Evaluasi Implementasi Audit Kasus Stunting (AKS) Dalam Rangka Percepatan Penurunan Stunting di Jawa Timur - Fanani, Abdul Fatah; Hazna Safira, Ulfia; Rosyadi Hamid, Imron (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2025)
Stunting Case Audit (AKS) is a strategic intervention under the national policy to accelerate stunting reduction in Indonesia. Its implementation at the regional level requires comprehensive evaluation. This study aims to assess the implementation of AKS in East Java Province based on the perspectives of implementers at various levels of government. A descriptive quantitative approach was employed, involving 743 respondents comprising members of Village/Kelurahan TPPS, Sub-district TPPS, District/City TPPS, Technical Teams, Expert Teams, and the Stunting Task Force. Data were collected through an online questionnaire and analyzed using descriptive statistics with the assistance of SPSS. The evaluation was guided by the Input-Process-Output model and the